Pharmacogenetics - Daly, Ann (Henry Stewart Talks, 2009)
Definition and history, CYP2D6 polymorphism, Pharmacogenetics of warfarin, Thiopurine methyltransferase, Genetics susceptibility to adverse drug reactions